Mapping the relationship between the structural deformation of a simply supported beam bridge and rail deformation in high-speed railways. (November 2020) - Jiang, Lizhong; Zheng, Lan; Feng, Yulin; Lai, Zhipeng; Zhou, Wangbao
By considering the effect of the constraints of the rails on the subgrade section on both sides of a bridge, analytical expressions are derived to study the mapping relationship between the rail deformation and changes in the condition of the supporting beam(s), based on the principle of minimum potential energy. Rail deformations in a slab track–bridge system induced by the subsidence of piers and beam faults are investigated in detail. Results are compared with the finite element calculations to assess the main factors that influence rail deformation. The results show that the rail deformation curves under different working conditions (single or multiple pier subsidence and beam faults) determined using the analytical model fit well with those from the finite element models. With increasing subsidence of piers, the rail deformed more significantly in the subsidence zone. Moreover, both the maximum downward and upward deformations of the rail changed linearly with the subsidence of piers. Use of fasteners or a mortar layer with greater vertical stiffness caused the rail to become more irregular.